Postharvest Quality and Decay Incidence among Tomato Fruit as Affected by Weather and Cultural Practices. - Jerry A. Bartz; Steven A. Sargent; John W. Scott (EDIS)
Postharvest decay losses for field-grown, fresh-market tomatoes are usually associated with harvests that occur when fields are wet and warm. During periods of persistently wet fields, decay pathogens infect damaged fruit on the plant as well as injuries to petioles and stems. Review of all reports and photos implicated excessive water in fruit rather than air temperatures as the primary predisposition. Excessive water in fruit is possible at virtually any time of the season and can appear at times of cold as well as warm field temperatures. This 8-page fact sheet was written by Jerry A. Bartz, Steven A. Sargent, and John W. Scott, and published by the UF Department of Plant Pathology, July 2012.